2017
DOI: 10.1590/1981-22562017020.160202
|View full text |Cite
|
Sign up to set email alerts
|

Health profile of family caregivers of the elderly and its association with variables of care: a rural study

Abstract: Objective: to analyze the profile of a population of caregivers from a city in a rural area of the state of São Paulo, Brazil, and identify their health complaints and the characteristics of care provided. Method: a prospective cross-sectional study was performed based on a domicile survey of 99 caregivers and their elderly care recipients. Information about the profile, context of care and health complaints of the caregivers was collected. The caregivers responded to the Zarit Burden Inventory and the Geriatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1
22

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 31 publications
2
33
1
22
Order By: Relevance
“…Another study showed that elderly caregivers living in rural areas, who achieved more than 16 points on the Zarit Burden Interview, lost about 5% of performance on a cognitive test. This same study reported that caregivers with medium or high levels of burden had a cognitive performance worse than caregivers with a lower level of burden 35 .…”
Section: Discussionmentioning
confidence: 76%
“…Another study showed that elderly caregivers living in rural areas, who achieved more than 16 points on the Zarit Burden Interview, lost about 5% of performance on a cognitive test. This same study reported that caregivers with medium or high levels of burden had a cognitive performance worse than caregivers with a lower level of burden 35 .…”
Section: Discussionmentioning
confidence: 76%
“…A study conducted in the United States with 46 informal caregivers revealed a dense daily routine with enduring and recurring tasks, such as changing bed rests from inappropriate settings, making it difficult to accommodate the patient to adequate postures (4) . A cross-sectional study carried out with 99 home caregivers with a mean age of 65.8 years showed that caring for the other for long periods, often without any support from third parties, interferes with health (5) .…”
Section: Introductionmentioning
confidence: 99%
“…1 These effects decrease the quality of care. Meta-analyses have shown that caregivers have higher levels of depression and burden and lower levels of subjective well-being and perceived health, especially women and spouses.…”
Section: Introductionmentioning
confidence: 99%